Stiefkinder der Entomologie in Mitteleuropa. - Klausnitzer, Bernhard (Contributions to Entomology = Beiträge zur Entomologie, 2006)
Reasons are summarised for the very different levels achieved in research on the distribution of insect orders occurring in Central Europe. Adequate information exists for only approximately just over one third of all species. A major part of the orders are at present barely being investigated, or not being worked on at all, e.g. the Protura, Diplura, Psocoptera, Phthiraptera, Sternorrhyncha, Siphonaptera, large subgroups of the Hymenoptera and Diptera. Even in the Lepidoptera and Coleoptera some families are hardly being studied, a fact which is often overlooked.